PERBANDINGAN ANTARA SISTEM PEMILU PROPORSIONAL TERBUKA DAN TERTUTUP DI INDONESIA: ANALISIS MENUJU PENYELENGGARAAN YANG LEBIH BAIK - John Kenedy Azis; Irene Eka Sihombing (Universitas Trisakti, 2023)
The electoral system is a crucial aspect in maintaining democracy and political participation in a country. In Indonesia, the debate regarding open and closed electoral systems continues. This article aims to analyze the comparison between these two electoral systems, focusing on their respective advantages and disadvantages. The research method employed is a comparative analysis, gathering data through literature review and analysis of elections in Indonesia. The analysis reveals that the open electoral system is more proportional, as it excels in expanding public participation, enhancing political representation, and strengthening party accountability. However, challenges in vote calculation and potential vote splitting still need to be addressed. In conclusion, this article argues that the open electoral system is more proportional compared to the closed system and holds the potential to enhance political participation in Indonesian society